Analisis Pengaruh Manajemen Aset Terhadap Kinerja Keuangan Perusahaan (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2016-2018) - Nur Diana Khalidah; Budi Wahono; Ety Saraswati (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTAssets management is needed to set management of assets companies that in line with the goal of the company which is to get maximum profits with minimum costs. This study was conducted to determine the effect of assets management measured with Inventory Turnover Ratio ( ITO ), Fixed Asset Turnover Ratio ( FATO ) and the total Asset Turnover Ratio ( TATO ) Towards performance of the financial measured with Return On Asset Ratio ( ROA ) The population and sampel in this study is the manufacturer company in industrial sector and consumption goods subsector food and beverages listed on the stock exchanges of indonesia during 2016-2018. Its technique is purposive sampling. There are 17 companies in accordance with the criteria of the research. Its method in the data collection uses documentation that in the form of its financial report of the company. Its analysis is double regressing with test hypothesis partial and simultan. The results of research is known that variable Management assets measured with Inventory Turnover Ratio ( ITO ), Fixed Asset Turnover Ratio ( FATO ) and the total Asset Turnover Ratio ( TATO ) influential on variable performance of the financial measured with Return On Asset Ratio ( ROA ). Key word: Inventory Turnover Ratio (ITO), Fixed Asset Turnover Ratio (FATO), Total Asset Turnover Ratio (TATO) dan Return On Asset Ratio (ROA)